STRATEGI SELF-MANAGEMENT UNTUK MENINGKATKAN KEDISIPLINAN BELAJAR - Faiqotul Isnaini (Jurnal Penelitian Humaniora, 2015)
The purpose of this study is to investigate the use of self-management strategies to improve students’ learning discipline. The study was taken place at SMP X Pati. It was an experimental research used Solomon Three Group Designs: the experimental group, control group 1, and control group 2. The number of subjects were 18 students of class VIII consisting of 6 students in each group. The data was collected using a scale of learning discipline and documentation. It was hypothesized that there was differences in learning discipline prior and after the use of self-management strategies. The intervention was given to group counseling with self-management strategies for 5 meetings. The result indicates that there was influence on learning discipline prior and after group counseling on self management strategy of the three groups seen from result of asymp. sig equal to 0,001. It means that group counseling on self-management strategy was effective to improve students’ learning discipline.